Common Linguistic Mistakes Made by Yemeni EFL Arabic-Speaking Learners in Their Writing - Ebtissam Ezzy Alwan Talib (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
Yemeni EFL students use a variety of communication skills, including writing, to interact with others. But because English is not their first language, many have difficulty writing. Provided that teaching English requires a variety of abilities, including writing. Since merging knowledge has made it more difficult for Yemeni EFL Arabic-speaking learners to succeed, this study aims to address common linguistic errors produced by these learners in their writing. Using surface approach taxonomy and mistake analysis, the study looks at linguistic errors made by Hodeidah University undergraduate students in order to provide writing skills recommendations. The study employs qualitative analysis, evaluating essay data from twenty Yemeni EFL eighth-semester Arabic-speaking students at Hodeidah University using Ellis' five-step error analysis (EA) approach. According to the research, omission is the most frequent error made in their works. The EA system entails gathering samples, identifying errors, comparing them to "correct," categorizing faults according to the Dulay et al. (1982) approach, and calculating the total number of errors. Out of 201 errors, 58.71% were in learners' writing, mainly due to intralingual transfer. Common errors included number markers, verb-tenses articles, prepositions, subject-verb agreements, and pronouns. Other common errors included word order, addition, and incorrect formation. Factors contributing to these errors include inter-linguistic comparisons between Arabic and English, auxiliary verb disregarding, inflectional morphemes, and verb conjugation components. After discussing the reasons for this study, its importance, analyzing the errors, and identifying the results, the researcher recommends language teachers provide ongoing feedback to prevent errors from becoming fossilized and encourage students to master the correct form of the target language.